Corrigendum to “Experimental analysis of the feasibility of low-cost piezoelectric diaphragms in impedance-based SHM applications” (Sensors and Actuators, A: Physical (2016) 238 (220–228)(S0924424715302703)(10.1016/j.sna.2015.11.031)) - Freitas, Everaldo Silva de [UNESP]; Baptista, Fabricio Guimarães [UNESP] (Elsevier, 2016)
The corresponding author regrets to inform that there was a small error in Equation 3. The subscript of the first variable in the denominator of the right side should be “S”; not “E”. The author would like to apologize for any inconvenience caused.